Multifaceted Factors Contributing to the Closure of Valley Forge Military Academy an Examination of Management, Economic, Legal, and Social Influences - ROSADO, Walter (Journal of Research in Educational Sciences; Vol 16 No 2 (2025): JRES, Volume XVI, Issue 2(20), Winter 2025DO - 10.14505/jres.v16.2(20).06, 2025)
This paper examines the rise and eventual closure of Valley Forge Military Academy (VFMA), a once-prominent American private military educational institution. Founded in 1928 and long celebrated for its unique Sandhurst-inspired traditions, VFMA faced escalating pressures from declining enrollment, rising operational costs, legal challenges, and shifting societal attitudes toward military education. Utilizing a mixed-methods approach, including alumni and faculty interviews and quantitative survey data, the study identifies key factors behind the academy’s decline, such as governance deficiencies, unsustainable financial practices, deferred maintenance, and reputation-damaging legal controversies. Drawing on theories of organizational failure and resilience, the analysis reveals how intertwined micro-level mismanagement, meso-level industry pressures, and macro-level external threats created a cumulative crisis that overwhelmed efforts at adaptation. Ultimately, VFMA’s experience underscores the vulnerability of small, tuition-dependent institutions to market legal, and cultural forces, offering broader lessons for organizational sustainability and resilience in the educational sector.